ASSESSING THE CHALLENGES AND OUTCOMES OF PERFORMING LAPAROSCOPIC SURGERY IN PATIENTS WITH OBESITY AND EXPLORING TECHNIQUES TO IMPROVE SAFETY AND EFFICACY - FARAZ, A; JAFFER, ZM; KHAN, TH; RAFIULLAH, .; GUL, A (Biological and Clinical Sciences Research Journal, 2024)
Obesity and the super-obesity population in the world are increasing, and an increasing number of subjects are going for bariatric surgery in an attempt to prevent the severe consequences associated with it. Objectives: The study's main objective is to assess the challenges and outcomes of performing laparoscopic surgery in patients with obesity and explore techniques to improve safety and efficacy. Methodology: This retrospective study was conducted at the General Surgery Division of MTI Lady Reading Hospital in Peshawar over four years, from 2020 to 2023. A total of 97 patients who underwent laparoscopic surgery during this period were included in the study. The subjects were chosen according to their suitability for laparoscopic procedures, with reference to the BMI standards for the definition of obesity. Results: Data were collected from 97 patients according to the study's criteria. The study included 97 patients with a mean age of 45.23 ± 3.85 years, with a gender distribution of 60% female and 40% male. The mean BMI was 34.5 kg/m², ranging from 30 to 42, indicating a population with significant obesity. In the study, intraoperative complications occurred in 15% of patients, with difficulty in visualization being the most common issue at 7%. Conversion to open surgery was necessary in 10% of cases, primarily due to inadequate visualization. Conclusion: It is concluded that performing laparoscopic surgery in obese patients presents significant challenges, including increased operative times, higher complication rates, and a greater likelihood of conversion to open surgery.